Divulge the Dual Challenge: A Case Report of Phenytoin Induced Dress Syndrome and Steroid-Induced Hyperglycaemia - Arumugakani, Vellaisamy; Seelan, Rajapandi Guna; Surendhar, Arjunan; Pradeeba, Ravi; Sairishika, Saikrishna; Harishankar, Ravichandran (Indian Journal of Pharmacy Practice)
Medication-induced skin and organ damage is an uncommon systemic reaction known as DRESS. This condition is caused by medication hypersensitivity and is linked to anticonvulsants, sulfur compounds, antidepressants, NSAIDs, and antibiotics it is tough to diagnose and cure, and reports of it are rare. The patient, a 35-year-old man, arrived at the hospital complaining of fever, lymphadenopathy, rashes, and itching. With history, the patient had neurosurgery done for a road accident in the parietal epidural Hematoma and started tablet phenytoin 100 mg 2 weeks before. The patient's clinical state was identified as phenytoin-induced DRESS syndrome based on the RegiSCAR scale, and the medicine responsible was withdrawn. Corticosteroids, antibiotics, and vitamin supplements were administered to the patient. On day 6, He developed hyperglycemia brought on by steroids; nevertheless, he was able to recover by taking a pill and a tapering dosage of injection methylprednisolone. Metformin 500 mg was provided, and the patient was discharged after symptoms gradually resolved. Early discovery and withdrawal of suspected medications are crucial for managing DRESS syndrome, which can be lethal.
Keywords: Phenytoin; DRESS syndrome; Methyl prednisolone; Hyperglycaemia.